HEALTH IMPACTS OF EXPOSURE TO NANOPARTICLES: ENVIRONMENTAL, HEALTH, AND SAFETY FACTORS TO TAKE INTO ACCOUNT WHILE EVALUATING RISKS AND DANGERS - Naif Ibrahim Nasser Amri, Owayed Abdullah R Al Khudhayr, Saleh Abdullah Alharbi, Moayad Musaddif Z Moafa, Bader Abdullah Thamer Alrashdi, Jamal Hamoud Ali Alrashdi, Sadeem Assad Ahmad Alshreehi; Sultanah Refaei Alajmi, Menawer Sayaah Menawer Alenazi, Fahad Hamoud Ali Alrashdi, Mariam Mohammed Almutiri, Somir Abdurhman Aftan Alhafi (Chelonian Research Foundation, 2022)
Research and development in material science is currently witnessing a dramatic expansion in the realm of nanotechnology. The majority of research efforts have been directed on applications; implications, or the effects on health and the environment, have received less attention. Ensuring the safety of products being produced from an environmental, health, and safety (EHS) perspective is crucial for the success of nanotechnology. Regarding this, research on pulmonary toxicity have previously indicated that as compared to bigger particles of same composition, lung exposures to ultrafine or nanoparticles—defined here as particles b 100 nm in one dimension—produce heightened unfavorable inflammatory responses. The toxicity of nanoparticles may be significantly influenced by surface characteristics, especially particle surface area, and the production of free radicals as a result of particle-cell interactions. Some of the most important elements for researching EHS risks and hazard effects associated with nanoparticle exposures are highlighted in this concise review. Hazard and exposure assessments lead to health and environmental risk assessments. The significance of particle characterization studies, the creation of a risk framework for nanomaterials, and corresponding hypothesis-driven, mechanistically-oriented investigations in tandem with base set hazard studies are the main points of discussion here. These studies clearly show that particle size is only one (and possibly a small) factor influencing the safety of nanomaterials. Keywords: Nanoparticle, Exposure, Risk, Safety, Characterization.